Targeted high-level production of chuangxinmycin and its halogenated derivatives with antitubercular activity - Xiongfang Zhao; Yuan Lu; Xintong Zhang; Xiumin Zhang; Yu Du; Xingli Han; Yuting Zhu; Wei Yu; Linzhuan Wu; Xingxing Li; Yuanyuan Shi; Tianyu Zhang; et al. (Microbial Cell Factories)
Abstract Background Chuangxinmycin (CM) is an old antibiotic from Actinoplanes tsinanensis CPCC, 200056, characterized by a dihydrothiopyrano[4,3,2-cd]indole scaffold and potent activity against Mycobacterium tuberculosis. Its congener norchuangxinmycin (NCM), which lacks antibacterial activity against various bacteria, unexpectedly retains antitubercular activity, indicating new mechanisms of action against M. tuberculosis in addition to tryptophan-tRNA synthetase inhibition. However, the variable low productivity and the limited number of active structural analogues represent a significant challenge for the future discovery and development of new anti-tuberculosis drugs involving CM and its derivatives. Results Based on the elucidation of CM biosynthetic pathway, we employed a stepwise strategy by combining heterologous expression, activator overexpression, promoter optimization and fermentation media screening to achieve directed and high-level production of CM and its congener NCM. The highest yields achieved were 301 mg/L (a 20.1-fold increase) for CM and 117.6 mg/L (a 13.7-fold increase) for NCM. Furthermore, eleven halogenated CM derivatives were obtained through precursor-directed biosynthesis, with six of them being purified and structurally confirmed by HR-MS, HR-MS/MS and NMR. Bioactivity testing against M. tuberculosis H37Rv and clinical isolates of isoniazid/rifampin-resistant M. tuberculosis showed potent activity for 5-F-CM and 7-F-NCM. Conclusions Synthetic biology techniques are well-suited for the targeted and high-level biosynthesis of CM and its derivatives. This study reports the highest laboratory-level yields of CM and NCM to date. This is the first instance of obtaining CM derivatives by biosynthesis rather than chemical synthesis, and it also marks the first report of halogenated NCM derivatives. High-level production of CM and its diverse analogues will provide a solid material foundation for advancing CM and its derivatives as potential anti-tuberculosis drug candidates.